Preparation method and structure of conductor material with high surface area

By forming a barrier layer on the support precursor and rupturing, and adding conductor materials, the problem of difficult to prepare high specific surface area conductor materials in the prior art is solved, and high-performance conductor materials are achieved, which are suitable for catalysts, adsorbents and energy storage fields.

CN119517632APending Publication Date: 2025-02-25TALENT HUB INVESTMENT CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311231363.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-25
Filing Date
2023-09-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to provide conductor materials with high specific surface area and cannot meet the high performance needs of catalysts, adsorbents and energy storage.

Method used

By forming a barrier layer on the outer surface of the support precursor and rupturing the partial barrier layer by rolling, partial outer surface of the support precursor is exposed, and then adding conductor material to connect the partial outer surface of the support precursor to form a high surface area conductor material.

Benefits of technology

The production of conductor materials with high specific surface area is achieved, suitable for catalysts, adsorbents and energy storage fields, especially in the application of supercapacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517632A_ABST
    Figure CN119517632A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a conductor material with a high surface area, which comprises the following steps of: forming a barrier layer on the outer surface of a support precursor (such as conductive nanofibers) to generate a mixed precursor, and rolling the mixed precursor to break the outer surface of the barrier layer part to generate a plurality of holes, so as to form the conductor material with the high surface area. And exposing the outer surface of the support precursor part at the openings, adding a conductor material to the mixed precursor, and contacting and electrically connecting the conductor material with the support precursor through the openings to obtain a high-surface-area conductor material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a preparation method and structure of a high surface area conductor material, and in particular to a preparation method and structure of a super capacitor material. Background Art

[0002] High surface area materials are materials with extremely large specific surface areas, and their industry is growing rapidly. The advantage of this type of material is its huge surface area to volume ratio, which makes it widely used in many fields.

[0003] The industrial development of high surface area materials involves many fields, such as catalysts, adsorbents and energy storage.

[0004] Continuing from the above, high surface area materials are often used as efficient catalysts. Due to their huge surface area, they can provide more active surfaces, thereby increasing the reaction rate and efficiency. Such materials have important applications in chemical synthesis, environmental protection and energy conversion, such as automobile exhaust purification, chemical reaction catalysis and fuel cells.

[0005] Continuing from the above, high surface area materials may have a large number of microscopic pores, and they often perform well in the adsorption and separation processes, which makes high surface area materials widely used in gas and liquid separation, water treatment, garbage disposal and other fields. For example, activated carbon is a common high surface area adsorption material that can be used to remove organic matter and heavy metal ions in water.

[0006] Continuing from the above, high surface area materials play an important role in the field of energy storage. For example, the electrode materials in supercapacitors and lithium-ion batteries often use porous materials with high surface areas to increase the charge transfer rate and capacitance, among which supercapacitors are a technology that has received much attention.

[0007] The appearance and structure of capacitors vary depending on their type. There are many commonly used capacitors on the market. Most capacitors contain at least two metal plates or metal conductor surfaces separated by a layer of insulating material. The conductor can be a metal foil, film, sintered metal beads or an electrolyte. Non-conductive insulating materials can increase the energy storage capacity of the capacitor. Common insulating materials are glass, ceramic, plastic film, paper, mica and metal oxides. Capacitors play an important role in many circuit applications.

[0008] Capacitors are widely used in electronic circuits. In terms of energy storage applications, they can be used as a substitute for batteries in some application areas. When high power output is required, capacitors are more suitable than batteries.

[0009] In summary, capacitors, as an important electronic component and power storage component, have the function of storing electrical energy and adjusting circuit characteristics. Different types of capacitors play a key role in different applications. From electronic equipment to power systems, the application of capacitors is indispensable. With the continuous development of science and technology, capacitors will continue to play an important role and promote progress and innovation in the field of electronics.

[0010] Continuing from the above, high dielectric constant ferroelectric materials in the temperature range of 25-200°C include barium titanate, lead magnesium niobate, and lead zirconate titanate, but lead-containing materials are volatile at high temperatures, easily react with electrodes, and are toxic, which limits their development. Therefore, barium titanate ceramics have become one of the most widely used dielectric materials for electronic ceramic capacitors.

[0011] With the development of the industry, more efficient high surface area materials are gradually needed in the fields of catalysts, adsorbents and energy storage. Especially in the field of energy storage, the high-value power storage market and power electronic equipment market are gradually developing in the direction of miniaturization and high performance, and in the direction of high energy storage density, high charge and discharge efficiency, easy processing and forming, and stable performance of dielectric materials. Therefore, the industry needs a method for preparing high surface area conductor materials to produce conductive materials with high specific surface area for application in the above-mentioned catalysts, adsorbents and energy storage fields.

[0012] In view of the above-mentioned problems of the conventional technology, the present invention provides a method for preparing a high surface area conductive material and its structure, wherein a barrier layer is formed on the outer surface of a supporting precursor, and then a portion of the barrier layer is ruptured by rolling to expose a portion of the outer surface of the supporting precursor, and a conductive material is added to connect the portion of the outer surface of the supporting precursor to form the desired high surface area conductive material. Summary of the invention

[0013] One object of the present invention is to provide a method for preparing a high surface area conductor material and its structure, which forms a barrier layer on the outer surface of a support precursor, and then partially breaks the barrier layer by rolling to expose a portion of the outer surface of the support precursor, and then adds a conductor material to connect the portion of the outer surface of the support precursor to form the desired high surface area conductor material.

[0014] In order to achieve the above-mentioned purposes and effects, the present invention provides a method for preparing a high surface area conductive material, the steps of which include: forming a barrier layer on the outer surface of a supporting precursor to produce a mixed precursor; rolling the mixed precursor, or using other strong mixing methods to break the outer surface of the barrier layer portion to produce a plurality of openings, so that the outer surface of the supporting precursor portion is exposed in the openings; adding a conductive material to the mixed precursor, and making the conductive material contact and electrically connect to the supporting precursor through the openings to obtain a high surface area conductive material; and manufacturing the high surface area conductive material in this way.

[0015] In order to achieve the above-mentioned purposes and effects, the present invention provides a structure of a high surface area conductor material, which includes: a substrate and a first high surface area conductor paste layer, the first high surface area conductor paste layer is arranged on the top of the substrate, the first high surface area conductor paste layer includes a first support precursor, a first barrier layer and a plurality of first particles, the first barrier layer covers the first support precursor, the first barrier layer is provided with a plurality of first openings, and the first particles are correspondingly arranged in the first openings; a high surface area conductor material is provided with this structure.

[0016] In one embodiment of the present invention, in the step of forming a barrier layer on the outer surface of a support precursor to produce a mixed precursor, the support precursor is added to a titanium tetrachloride solution to form the barrier layer on the outer surface of the support precursor to produce the mixed precursor.

[0017] In one embodiment of the present invention, a barrier layer is formed on the outer surface of a support precursor, and in the step of producing a mixed precursor, the mixed precursor is added to a barium acetate solution, and the barium acetate in the barium acetate solution is combined with a titanium oxide in the barrier layer to form barium titanate.

[0018] In one embodiment of the present invention, in the step of adding a conductor material to the mixed precursor and making the conductor material contact and electrically connect to the support precursor through the openings to obtain a conductor material with a high surface area, the conductor material comprises a polyvinyl butyral solution, a conductive adhesive and barium titanate particles. During rolling, the barrier layer is cracked to produce the openings, and the conductive adhesive and the barium titanate particles are contacted and electrically connected to the support precursor through the openings to obtain the conductor material with a high surface area.

[0019] In one embodiment of the present invention, after adding a conductor material to the mixed precursor and making the conductor material contact and electrically connect to the support precursor through the openings to obtain a high surface area conductor material, the method further includes the steps of: coating the high surface area conductor material on the upper and lower sides of a substrate and heating it to a sintering temperature; forming a capacitor.

[0020] In one embodiment of the present invention, the support precursor comprises a carbon nanotube (CNT) or a metal nanofiber.

[0021] In one embodiment of the present invention, the polyvinyl butyral solution comprises polyvinyl butyral (PVB), toluene (C 7 H 8 ) and ethanol (CH 3 CH 2 OH) as a binder and solvent.

[0022] In one embodiment of the present invention, in the step of forming a barrier layer on the outer surface of a supporting precursor to produce a mixed precursor, the barrier layer is formed on the outer surface of the supporting precursor by one or any combination of hydrothermal synthesis, electroplating, sputtering (PVD) and chemical vapor deposition (CVD).

[0023] In one embodiment of the present invention, the sintering temperature is between 1000°C and 1350°C.

[0024] In one embodiment of the present invention, it further includes a second high surface area conductor paste layer, which is disposed below the substrate. The second high surface area conductor paste layer includes a second supporting precursor, a second barrier layer and a plurality of second particles. The second barrier layer covers the second supporting precursor. The second barrier layer is provided with a plurality of second openings, and the second particles are correspondingly disposed in the second openings.

[0025] In one embodiment of the present invention, the first support precursor and the second support precursor include a carbon nanotube (CNT) or a nanometal fiber.

[0026] In one embodiment of the present invention, the first barrier layer and the second set of barrier layers are barium titanate.

[0027] In one embodiment of the present invention, the first particles and the second particles are metal particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 : It is a schematic diagram of the material manufacturing steps of one embodiment of the present invention; FIG. 2A to FIG. 2D : It is a schematic diagram of the material structure of an embodiment of the present invention; Figure 3 : It is a schematic diagram of the steps of manufacturing a capacitor material according to an embodiment of the present invention; Figure 4 :It is a schematic diagram of the application steps of an embodiment of the present invention; and Figure 5 : It is a schematic diagram of a capacitor structure of an embodiment of the present invention.

Figure number comparison

[0029] In order to further understand and appreciate the structural features and effects of the present invention, a preferred embodiment and detailed description are provided as follows:

[0030] In view of the above-mentioned problems of the conventional technology, the present invention is a method for preparing a high surface area conductive material and its structure, wherein a barrier layer is formed on the outer surface of a supporting precursor, and then a portion of the barrier layer is broken by rolling or strong mixing to expose a portion of the outer surface of the supporting precursor, and a conductive material is added to connect the portion of the outer surface of the supporting precursor to form the desired high surface area conductive material, thereby solving the urgent need of the conventional technology for materials with a high specific surface area to meet the application needs of the industrial market.

[0031] See also Figure 1 , which is a schematic diagram of the material manufacturing steps of an embodiment of the present invention. As shown in the figure, in this embodiment, it is a method for preparing a high surface area conductor material, and the steps include:

[0032] Step S02: forming a barrier layer on the outer surface of the support precursor to produce a mixed precursor;

[0033] Step S04: rolling the mixed precursor to rupture the outer surface of the barrier layer to generate a plurality of openings, so that the outer surface of the supporting precursor is exposed in the openings;

[0034] Step S06: adding a conductive material to the mixed precursor, and allowing the conductive material to contact and electrically connect to the supporting precursor through the openings to obtain a conductive material with a high surface area.

[0035] See again Figure 1 as well as FIG. 2A to FIG. 2D , FIG. 2A to FIG. 2D Schematic diagram of the material structure of an embodiment of the present invention, as shown in FIG. 2A to FIG. 2BAs shown, in step S02 of this embodiment, a barrier layer 14 is formed on the outer surface of a support precursor 12, that is, the barrier layer 14 is coated on the outer surface of the support precursor 12 to produce a mixed precursor 16. The barrier layer 14 can prevent the fibers in the support precursor 12 from being entangled, collapsed or adhered to each other, thereby reducing the surface area of ​​the support precursor 12.

[0036] Continuing from the above, in one embodiment, the support precursor 12 includes a carbon nanotube (CNT) or a nanometal fiber, wherein the nanometal fiber (the metal may be copper, silver, nickel), but this embodiment is not limited thereto.

[0037] Continuing from the above, in one embodiment, the barrier layer 14 can be formed on the outer surface of the support precursor 12 by using one or any combination of hydrothermal synthesis, electroplating, sputtering (PVD) and chemical vapor deposition (CVD), but this embodiment is not limited thereto.

[0038] See again Figure 1 as well as FIG. 2A to FIG. 2D As shown in the figure, in step S04 of the present embodiment, after the mixed precursor 16 is formed as in the above steps, the mixed precursor 16 is rolled and an external force is applied to the mixed precursor 16 to bend and deform the supporting precursor 12 and the barrier layer 14 of the mixed precursor 16, so that the outer surface of the barrier layer 14 is partially broken, and a plurality of openings 142 are generated on the outer surface of the barrier layer 14, so that the outer surface of the supporting precursor 12 is exposed in the openings 142.

[0039] Continuing from the above, in this embodiment, the openings 142 are formed after the barrier layer 14 is deformed and elastically restored, so that the support precursor 12 is exposed to the openings 142 .

[0040] See again Figure 1 as well as FIG. 2A to FIG. 2D As shown in the figure, in step S06 of this embodiment, a conductive material 18 is added to the mixed precursor 16, and the conductive material 18 is contacted and electrically connected to the support precursor 12 through the openings 142. Since the conductive material 18 is electrically connected to the support precursor 12 on the inner side of the barrier layer 14, the surface area of ​​the support precursor 12 in contact with the outer side is increased, thereby obtaining a conductive material with a high surface area.

[0041] Continuing from the above, in this embodiment, the conductive material 18 is a metal conductive paste, and the conductive material 18 is further interconnected, so that each fiber of the support precursor 12 is electrically connected to each other, further becoming the specific surface area of ​​the high surface area conductive material.

[0042] The method for preparing the high surface area conductor material of this embodiment can manufacture the high surface area conductor material with a high specific surface area, which can be applicable to application requirements of different industrial markets, such as catalyst materials and supercapacitors.

[0043] See also Figure 3 , which is a schematic diagram of the steps of manufacturing capacitor materials according to an embodiment of the present invention. As shown in the figure, this embodiment is based on the above embodiment. This embodiment is applied to a method for preparing capacitor materials, and the steps include:

[0044] Step S11: adding a support precursor to a titanium tetrachloride solution and heating the solution to a first temperature and a first time to form a barrier layer on the outer surface of the support precursor to produce a mixed precursor;

[0045] Step S13: washing and drying the mixed precursor;

[0046] Step S15: adding the mixed precursor to the barium acetate solution and heating it to a second temperature and a second time, so that the barium acetate in the barium acetate solution is combined with the titanium oxide of the barrier layer to form barium titanate;

[0047] Step S17: washing and drying the mixed precursor; and

[0048] Step S19: adding barium titanate particles, conductive glue and mixed precursor to the polyvinyl butyral solution, and rolling and mixing to rupture the barrier layer to generate the openings, so that the conductive glue particles fill the openings, and the barium titanate particles contact and electrically connect to the supporting precursor through the openings to obtain a high surface area conductor material.

[0049] See again Figure 3 As shown in the figure, in step S11 of this embodiment, after the support precursor is added to a titanium tetrachloride solution, the support precursor and the titanium tetrachloride solution are mixed, and the support precursor and the titanium tetrachloride solution are heated at a first temperature. After heating for a first time, the titanium tetrachloride solution reacts with oxygen to form titanium oxide on the outer surface of the support precursor to form the barrier layer, thereby generating the mixed precursor.

[0050] Continuing from the above, in this embodiment, the supporting precursor uses a carbon nanotube (CNT), and the supporting precursor includes a plurality of carbon nanotubes. The carbon nanotubes are uniformly mixed with the acidic solution and the titanium tetrachloride, and the carbon nanotubes, the acidic solution and the titanium tetrachloride are heated to form the first mixed solution. The acidic solution softens the carbon nanotubes and increases the surface activity, allowing titanium to adhere to the surface of the carbon nanotubes.

[0051] Continuing from the above, in one embodiment, the support precursor may also use a nanometal fiber, which prefabricates nanometal (e.g., copper, silver, nickel) into a plurality of nano-sized metal wires, then uniformly mixes the nanometal with the acid solution and the titanium tetrachloride, and heats the nanometal, the acid solution and the titanium tetrachloride to form the first mixed solution. The acid solution enhances the surface activity of the nanometal, allowing titanium to adhere to the surface of the nanometal fiber.

[0052] Continuing from the above, in one embodiment, the support precursor may be first cleaned with an acidic solution to remove impurities on the outer surface of the support precursor. The acidic solution may be nitric acid, but is not limited thereto. A suitable acidic solution may be selected based on the material of the support precursor used.

[0053] Continuing from the above, in this embodiment, the titanium tetrachloride (TiCl 4 ) produces intermediates of titanium oxide and its compounds.

[0054] Continuing from the above, in this embodiment, the first temperature and the first time vary according to the material properties of the support precursor and the titanium tetrachloride solution. For example, in the above-mentioned embodiment of carbon nanotubes and titanium tetrachloride, the first temperature is between 80° C. and 100° C., and the first time is between 0.5 and 8 hours. For example, the mixed solution of the support precursor and the titanium tetrachloride solution is heated at 90° C. and heated for 0.5 to 10 hours.

[0055] Continuing from the above, in one embodiment, an ultrasonic vibrator is used to vibrate the acid solution, the support precursor and the titanium tetrachloride mixture for 1 to 2 hours to achieve a uniform mixing effect.

[0056] See again Figure 3 As shown in the figure, in step S13 of this embodiment, the mixed precursor is further washed with deionized water and ethanol until the pH value is neutral (for example, to remove the hydrochloric acid produced by the reaction of titanium tetrachloride to titanium oxide), and the mixed precursor is dried in an oven.

[0057] Continuing from the above, in the above-mentioned example of carbon nanotubes and titanium tetrachloride, the mixed precursor is titanium oxide-carbon nanotubes (TiO 2 -CNT) precursor.

[0058] Continuing from the above, in this embodiment, the mixed precursor is dried at 50°C to 70°C.

[0059] See again Figure 3As shown in the figure, in step S15 of this embodiment, the mixed precursor is added to a barium acetate solution and heated to a second temperature and a second time, so that the barium acetate of the barium acetate solution is combined with the titanium oxide (such as titanium oxide) of the barrier layer to form barium titanate.

[0060] Continuing from the above, in this embodiment, the second temperature and the second time vary according to the material properties of the barium acetate solution and the mixed precursor. For example, in the above-mentioned embodiment of the barium acetate solution and the mixed precursor, the second temperature is between 150° C. and 170° C., and the second time is between 0.5 and 10 hours. For example, the mixed solution of the barium acetate solution and the mixed precursor is heated at 160° C. and heated for 0.5 to 10 hours to allow the substances of the mixed precursor and the barium acetate solution to fully combine.

[0061] Continuing from the above, in one embodiment, an ultrasonic vibrator is used to vibrate the barium acetate solution and the mixed precursor mixture for 1 to 2 hours to achieve a uniform mixing effect.

[0062] Continuing from the above, in one embodiment, the mixed precursor is further washed with deionized water and ethanol until the pH value is neutral.

[0063] See again Figure 3 As shown in the figure, in step S17 of this embodiment, the mixed precursor is dried in an oven.

[0064] Continuing from the above, in the above-mentioned examples of the barium acetate solution and the mixed precursor, the barium acetate solution and the mixed precursor are combined to form a barium titanate-coated carbon nanotube (BaTiO 3 -CNT) precursor.

[0065] Continuing from the above, in this embodiment, the mixed precursor is dried at 50°C to 70°C.

[0066] See again Figure 3 As shown in the figure, in step S19 of this embodiment, the conductive material includes a polyvinyl butyral solution, a conductive glue and barium titanate particles. The barium titanate particles, the conductive glue and the mixed precursor are added to the polyvinyl butyral solution, and rolled and mixed to cause the barrier layer to crack and generate the openings, so that the particles of the conductive glue fill the openings of the barrier layer of the mixed precursor (such as Figure 2D ), so that the conductive fiber (in this embodiment, carbon nanotube CNT) contacts and electrically connects to the outer surface of the support precursor through the openings, and finally the high surface area conductor material is obtained.

[0067] Continuing from the above, in this embodiment, the polyvinyl butyral solution comprises polyvinyl butyral (PVB), toluene (C 7 H 8) and ethanol (CH 3 CH 2 OH), wherein the toluene (C 7 H 8 ) and the ethanol (CH 3 CH 2 OH) in a volume ratio of 3:2 to form a solution, and then the polyvinyl butyral (PVB) is added to form the polyvinyl butyral solution.

[0068] See also Figure 4 , which is a schematic diagram of the application steps of an embodiment of the present invention. As shown in the figure, after adding a conductor material to the mixed precursor and rolling and mixing so that the conductor material contacts and electrically connects the support precursor through the openings to obtain a high surface area conductor material, the process further includes the following steps:

[0069] Step S22: coating a high surface area conductor material on the substrate and heating it to a sintering temperature;

[0070] Step S24: forming a capacitor;

[0071] See again Figure 4 As shown in the figure, in step S22 of this embodiment, the high surface area conductive material is coated on a substrate 10 .

[0072] See again Figure 4 As shown in the figure, in step S24 of this embodiment, the high surface area conductive material is coated under a substrate 10 and heated to the sintering temperature to form a capacitor.

[0073] See also Figure 5 , which is a schematic diagram of a capacitor structure according to an embodiment of the present invention. As shown in the figure, this embodiment is based on the above-mentioned embodiment of the material preparation method applied to capacitors. In this embodiment, the mixed precursor is tested by a viscosity machine. After reaching a suitable viscosity, the mixed precursor is further rolled and crushed to slightly damage the barrier layer on the outside of the supporting precursor to produce the openings.

[0074] Continuing from the above, in one embodiment, a three roll mill (Triple roll mill) is used to roll and mix the capacitor slurry.

[0075] See again Figure 5As shown in the figure, in this embodiment, the capacitor slurry is coated on the upper and lower sides of the substrate 10, the capacitor slurry is coated on the upper side of the substrate 10 to form a first high surface area conductor slurry layer 20, and the capacitor slurry is coated on the lower side of the substrate 10 to form a second high surface area conductor slurry layer 30. The substrate 10, the first high surface area conductor slurry layer 20 and the second high surface area conductor slurry layer 30 form a capacitor precursor, which is fired at a high temperature to form a capacitor product.

[0076] Continuing from the above, in this embodiment, the substrate 10 is a barium titanate or metal oxide ceramic substrate, such as a substrate containing barium or various dielectric materials, for combining with the high surface area conductive paste.

[0077] Continuing from the above, in this embodiment, the first high surface area conductive paste layer 20 comprises a plurality of first support precursors 22 and a plurality of first particles 24. In one embodiment, the first support precursors 22 are carbon nanotubes (CNTs), and the second support precursors 32 are coated with a first barrier layer 23 (e.g., barium titanate (BaTiO 3 )), the first particles 24 are metal particles of the conductive paste, but the present embodiment is not limited thereto.

[0078] Continuing from the above, in this embodiment, the second high surface area conductive paste layer 30 comprises a plurality of second support precursors 32 and a plurality of second particles 34. In one embodiment, the second support precursors 32 are carbon nanotubes (CNTs), and the second support precursors 32 are coated with a second barrier layer 33 (e.g., barium titanate (BaTiO 3 )), the second particles 34 are metal particles of the conductive paste, but this embodiment is not limited thereto.

[0079] See again Figure 5 As shown in the figure, in this embodiment, the intermediate product is heated to a third temperature, and the third temperature is the sintering temperature of the second mixture and the substrate 10 .

[0080] Continuing from the above, in the above-mentioned embodiment of barium titanate-carbon nanotubes (BaTiO3-CNT), the third temperature is between 1000°C and 1350°C, and the intermediate product is further heated to between 240°C and 260°C for 2 to 2.5 hours, and then the intermediate product is heated to between 1000°C and 1350°C for 2 to 2.5 hours.

[0081] In summary, the present invention provides a method for preparing a high surface area conductor material, wherein a barrier layer is formed on the outer surface of a support precursor, and then a portion of the barrier layer is ruptured by rolling to expose a portion of the outer surface of the support precursor, and a conductor material is added to connect the portion of the outer surface of the support precursor to form the desired high surface area conductor material to form a capacitor structure, thereby solving the problem that conventional technology urgently needs supercapacitor materials to adapt to market and environmental changes in the industry.

[0082] The order of execution of each step in the above embodiment does not mean the order of execution. The order of execution of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiment of the present application.

[0083] The above is only a preferred embodiment of the present invention and is not intended to limit the scope of the present invention. All equivalent changes and modifications to the shape, structure, characteristics and spirit described in the claims of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a high surface area conductor material, characterized in that: The steps include: forming a barrier layer on the outer surface of a support precursor to produce a mixed precursor; Rolling the mixed precursor to break the outer surface of the barrier layer to generate a plurality of openings, so that the outer surface of the support precursor is exposed in the openings; as well as A conductor material is added to the mixed precursor, and the conductor material is contacted and electrically connected to the support precursor through the openings to obtain a high surface area conductor material.

2. The method for preparing a high surface area conductor material according to claim 1, characterized in that: In the step of forming a barrier layer on the outer surface of a support precursor to produce a mixed precursor, the support precursor is added into a titanium tetrachloride solution to form the barrier layer on the outer surface of the support precursor to produce the mixed precursor.

3. The method for preparing a high surface area conductor material according to claim 2, characterized in that: In the step of forming a barrier layer on the outer surface of a supporting precursor and producing a mixed precursor, the mixed precursor is added to a barium acetate solution, and the barium acetate in the barium acetate solution is combined with a titanium oxide in the barrier layer to form barium titanate.

4. The method for preparing a high surface area conductor material according to claim 3, characterized in that: In the step of adding a conductor material to the mixed precursor and making the conductor material contact and electrically connect to the support precursor through the openings to obtain a conductor material with a high surface area, the conductor material comprises a polyvinyl butyral solution, a conductive glue and barium titanate particles. During rolling, the barrier layer is cracked to generate the openings, and the conductive glue and the barium titanate particles are contacted and electrically connected to the support precursor through the openings to obtain the conductor material with a high surface area.

5. The method for preparing a high surface area conductor material according to claim 1, characterized in that: After adding a conductor material to the mixed precursor and making the conductor material contact and electrically connect to the support precursor through the openings to obtain a conductor material with a high surface area, the method further comprises the following steps: The high surface area conductor material is coated on the upper and lower sides of a substrate and heated to a sintering temperature; and A capacitor is formed.

6. The method for preparing a high surface area conductor material according to claim 1 or 4, characterized in that: The support precursor includes a carbon nanotube (CNT) or a nanometal fiber.

7. The method for preparing a high surface area conductor material according to claim 4, characterized in that: The polyvinyl butyral solution includes polyvinyl butyral (PVB), toluene (C7H8) and ethanol (CH3CH2OH).

8. The method for preparing a high surface area conductor material according to claim 1, characterized in that: In the step of forming a barrier layer on the outer surface of a support precursor to produce a mixed precursor, the barrier layer is formed on the outer surface of the support precursor by one or any combination of hydrothermal synthesis, electroplating, sputtering (PVD) and chemical vapor deposition (CVD).

9. The method for preparing a high surface area conductor material according to claim 5, characterized in that: The sintering temperature is between 1000°C and 1350°C.

10. A structure of high surface area conductor material, characterized in that It contains: a substrate; as well as A first high surface area conductor paste layer is disposed on the substrate, the first high surface area conductor paste layer comprises a first support precursor, a first barrier layer and a plurality of first particles, the first barrier layer covers the first support precursor, the first barrier layer is provided with a plurality of first openings, and the first particles are correspondingly disposed in the first openings.

11. The structure of high surface area conductor material according to claim 10, characterized in that It further includes a second high surface area conductor paste layer, which is disposed below the substrate. The second high surface area conductor paste layer includes a second support precursor, a second barrier layer and a plurality of second particles. The second barrier layer covers the second support precursor. The second barrier layer is provided with a plurality of second openings, and the second particles are correspondingly disposed in the second openings.

12. The structure of high surface area conductor material according to claim 11, characterized in that The first support precursor and the second support precursor include a carbon nanotube (CNT) or a nanometal fiber.

13. The structure of high surface area conductor material according to claim 11, characterized in that The first barrier layer and the second set of barrier layers are barium titanate.

14. The structure of high surface area conductor material according to claim 11, characterized in that The first particles and the second particles are metal particles.